Cooking with the Cat - Worth, Bonnie; Moroney, Christopher; Seuss (New York : Random House, 2003)
The Cat in the Hat bakes cupcakes in this simple retelling of a scene from the movie version of Dr. Seuss's classic book.
Keywords: Cooking; Cats; Stories in rhyme